A further study on the Belisana spiders (Araneae: Pholcidae) from Xishuangbanna, Yunnan, China - Zhao, Fangyu; Yang, Lan; Li, Shuqiang; Zheng, Guo; Yao, Zhiyuan (Zootaxa, 2023)
Species of the spider genus Belisana Thorell, 1898 exhibit high diversity in Xishuangbanna, Yunnan, China. Currently, 14 species have been recorded. In this study, three additional new species of Belisana from Xishuangbanna are described and illustrated based on specimens from the collection of Shenyang Normal University in China. They are: Belisana chuandiani Li, Zheng & Yao sp. nov. (male, female), B. daxiangi Li, Zheng & Yao sp. nov. (male), and B. fengzheni Li, Zheng & Yao sp. nov. (male, female). Moreover, the female of B. zhengi Yao, Pham & Li, 2015 is reported for the first time. Taxonomic keys for identification of males and females of Belisana species from Xishuangbanna are also presented.